Stress and memory: a systematic state-of-the-art review with evidence-gathering recommendations for police. Issue 1 (9th December 2020) - Di Nota, Paula M.; Stoliker, Bryce E.; Vaughan, Adam D.; Andersen, Judith P.; Anderson, Gregory S.
Abstract : Purpose: The purpose of this study isto synthesize recent empirical research investigating memory of stressful critical incidents (both simulated and occurring in the field) among law enforcement officers. Design/methodology/approach: The study used the approach of systematic state-of-the-art review. Findings: In total, 20 studies of police and military officers show reduced detail and accuracy of high- versus low-stress incidents, especially for peripheral versus target information. Decrements in memory performance were mediated by the extent of physiological stress responses. Delayed recall accuracy was improved among officers that engaged in immediate post-incident rehearsal, including independent debriefing or reviewing body-worn camera footage. Research limitations/implications: Most studies were not found through systematic database searches, highlighting a need for broader indexing and/or open access publishing to make research more accessible. Practical implications: By understanding how stress physiology enhances or interferes with memory encoding, consolidation and recall, evidence-based practices surrounding post-incident evidence gathering are recommended. Social implications: The current review addresses common public misconceptions of enhanced cognitive performance among police relative to the average citizen. Originality/value: The current work draws from scientific knowledge about the pervasive influence of stress physiology on memory to inform existing practices surrounding post-incident evidence gathering among police.